2011
DOI: 10.1002/hed.21698
|View full text |Cite
|
Sign up to set email alerts
|

Novel head and neck cancer survival analysis approach: Random survival forests versus cox proportional hazards regression

Abstract: Both approaches delivered similar error rates. The Cox model gives a clinically understandable output on covariate impact, whereas RSF becomes more of a "black box." RSF complements the Cox model by giving more insight and confidence toward relative importance of model covariates. RSF can be recommended as the approach of choice in automating survival analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 16 publications
3
48
0
Order By: Relevance
“…These findings are in line with other studies that used support vector machines for analyzing survival [3]–[6]. On the other hand, our findings also support the results of previous studies that relied on Cox regression modeling to predict the five year mortality and the overall mortality of newly diagnosed patients with HNSCC [15][17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are in line with other studies that used support vector machines for analyzing survival [3]–[6]. On the other hand, our findings also support the results of previous studies that relied on Cox regression modeling to predict the five year mortality and the overall mortality of newly diagnosed patients with HNSCC [15][17].…”
Section: Discussionsupporting
confidence: 92%
“…Predictors in this model included Tumor location, Age at diagnosis, Gender, T-N-M classification (T = the extent of the primary tumor, N = the absence or presence and extent of regional lymph node metastasis, M = the absence or presence of distant metastasis) and Prior malignancies. In 2010, Datema et al [16], [17] published an updated model including comorbidity according to the Adult Comorbidity Evaluation, based on a 27-item comorbidity index (ACE27) [18]. In our study, we excluded patients for whom comorbidity was unknown, resulting in a total of 1282 patients .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of mentioned studies in the context of learning algorithms, there are also comparisons between RSF and Cox, as the most widely used method for modeling the censored data (Hothorn, Bühlmann, Dudoit, Molinaro, & Van Der Laan, 2006). Through some of these comparative studies Cox has shown, not only the same (Hsich et al, 2011), but also better performance than all diversity of forests (Datema et al, 2012). Additionally, the supremacy of Cox has been confirmed by other simulation studies (Kurt Omurlu et al, 2009).…”
Section: Discussionmentioning
confidence: 77%
“…For instance comparative studies, using both of RSF and Cox proportional hazard, for modeling the survival of patients with different cancers as breast (Kurt Omurlu, Ture, & Tokatli, 2009), prostate (Gerds, Kattan, Schumacher, & Yu, 2013), head and neck (Datema et al, 2012), as well as patients with systolic heart failure (Hsich, Gorodeski, Blackstone, Ishwaran, & Lauer, 2011). Forests were also compared with variety of learning techniques (Mirmohammadi, Shishehgar, & Ghapanchi, 2014;Pang, Datta, & Zhao, 2010) and survival trees, as the forest elements (Yosefian, Mosa Farkhani, & Baneshi, 2015); but as far as we know, the RSF has never been compared with MoBRP.…”
Section: Introductionmentioning
confidence: 99%